Bring back Terrorist into the Society: How Indonesia Deradicalize the Terrorist - Rachmawati, Fairus Augustina (Semarang State University Undergraduate Law and Society Review, 2022)
Southeast Asia is home to one-third of the largest Muslim population in the world. About 87% of Indonesia's population is Muslim, making it the majority religion in Indonesia. In Indonesia Terrorism is a threat that everyone knows that the form of crime is very dangerous, not only in Indonesia but also in different countries. As an example of the Bali Bombing case in 2002 has become the most important lesson for Indonesia, not only concerning the investigation and investigation of terrorism cases, but also how the de-radicalization effort becomes an important part in fighting terrorism. Entering the reform era, radical ideology has more free space to threaten national security. The problem at this time is that the synergy between TNI-Polri-Sipil is still often troubled, whether it is directly related to operations or not. Preventing terrorism is more meaningful, compared to the ability to arrest terrorists who have carried out bombings that killed tens or hundreds of people. Then, anyone who needs to be involved in a de-radicalization program to prevent the loss of lives and wounds that are in vain.